Causal Inference and Machine Learning in Practice with EconML and CausalML: Industrial Use Cases at Microsoft, TripAdvisor, Uber - Syrgkanis, Vasilis; Lewis, Greg; Oprescu, Miruna; Hei, Maggie; Battocchi, Keith; Dillon, Eleanor; Pan, Jing; Wu, Yifeng; Lo, Paul; Chen, Huigang; Harinen, Totte; Lee, Jeong-Yoon (2021 Knowledge Discovery and Data Mining, 2021)
In recent years, both academic research and industry applications see an increased effort in using machine learning methods to measure granular causal effects and design optimal policies based on these causal estimates. Open source packages such as CausalML and EconML provide a unified interface for applied researchers and industry practitioners with a variety of machine learning methods for causal inference. The tutorial will cover the topics including conditional treatment effect estimators by meta-learners and tree-based algorithms, model validations and sensitivity analysis, optimization algorithms including policy leaner and cost optimization. In addition, the tutorial will demonstrate the production of these algorithms in industry use cases.